Linfomas Double-Hit em casuística de Linfomas Não-Hodgkin B de alto grau: estudo clínico, morfológico, imunoistoquímico e citogenético - Oliveira, Cristiano Claudino [UNESP] (2015)
Background: Double-Hit Lymphomas (DHL) are rare high-grade neoplasms characterized by the translocation of gene MYC to other translocations involving genes BCL2 and/or BCL6, whose diagnosis depends on the cytogenetic examination, a technique with low availability and high cost. Therefore, it has been valued the identification of morphologic and/or immunophenotypic factors that have association with the detection of those translocations. Objectives: To identify DHL patients in group of high grade non-Hodgkin lymphoma (NHL-B) and evaluate the associations between the cytogenetic and immunohistochemical (IHC) results for the MYC, BCL2 and BCL6 markers. Design: Clinical and morphological review of 120 patients diagnosed with diffuse large B-cell lymphoma (DLBCL) and Burkitt lymphoma (BL) was proceeded, with production of a tissue microarray platform (TMA) to perform IHC (CD20, CD79a, PAX5, CD10, BCL6, BCL2, MUM1, TDT and c-MYC) and fluorescence in situ hybridization (FISH) for detection of c-MYC, BCL2 and BCL6 gene translocations. Results: Three patients with DHL were detected: two with translocations of MYC and BCL2 and one with translocations of MYC and BCL6, all leading to death in less than six months. Among 90 cytogenetically evaluable samples, associations were determined between IHC and FISH for MYC (p=0.036) and BCL2 (p=0.001), though with regular compliance testing, indicated by Kappa value of 0.23 [0.0;0.49] and 0.35 [0.13;0.56], respectively. In the DLBCL group (n=72), MYC, BCL6 and BCL2 translocations were present in 4.1%, 12.5% and 15.2%, respectively. Starry sky morphology was strongly associated with MYC positivity (p=0.01). Conclusion: The detection of only three DHL patients in this series, all evolving to death, confirms the rarity and aggressiveness of this neoplasm. The morphological pattern starry sky and the expression by IHC of MYC and BCL2 can represent possible selection factors for the ...